Performance trends in continuous assessments: a case study of engineering students in a statistics course - Mahlan, Siti Balqis; Hamat, Muniroh; Shamsuddin, Maisurah; Alias, Fadzilawani Astifar (Unit Penerbitan JSKM, 2025)
This case study describes and compares the academic performance of engineering students enrolled in the Statistics for Science and Engineering course, focusing on three formative assessments: a quiz, a group assignment, and a test. A total of 43 students from Mechanical, Electrical, and Chemical Engineering programs participated, representing academic semesters from Semester 5 to Semester 9. Descriptive statistics were used to analyse score distributions and identify performance patterns across programs and assessment types. The findings show variations in achievement, with Mechanical Engineering students generally outperforming others. These results highlight the need for targeted teaching approaches based on program-specific learning needs. In conclusion, understanding performance trends can help educators enhance assessment design and support student learning more effectively.